Metamorphosis : [a thesis presented in partial fulfilment of the requirements for the degree of Master of Design at Massey University, Wellington] - Kreft, Steffen (Massey University, 2009)
No abstract available
Keywords: Metamorphosis; Bildungsroman; Personal development; Journey; Travel; Research through design; Surrealistic film; Fields of Research::410000 The Arts::410300 Cinema, Electronic Arts and Media Studies::410301 Film and video studies